2021
DOI: 10.1021/acsami.1c02443
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Design Rules for Optimizing the Interface between Immobilized Enzymes and Random Copolymer Brushes

Abstract: A long-standing goal in the field of biotechnology is to develop and understand design rules for the stabilization of enzymes upon immobilization to materials. While immobilization has sometimes been successful as a strategy to stabilize enzymes, the design of synthetic materials that stabilize enzymes remains largely empirical. We sought to overcome this challenge by investigating the mechanistic basis for the stabilization of immobilized lipases on random copolymer brush surfaces comprised of poly­(ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 65 publications
(110 reference statements)
2
38
0
Order By: Relevance
“…302,326 Very recent advances in surface-sensitive spectroscopic techniques have provided evidence that push the determination of enzyme structure and orientation at the solid-liquid interface, in particular single-molecule studies showing that analyses sensitive to temporal and spatial heterogeneities in immobilized enzymes are useful to explain the effects of conformational stability and active-site accessibility on activity. 302,[504][505][506][507] In the interplay with the structural aspects of the immobilized enzyme the microenvironment is the other fundamental aspect determining enzyme performance. The microenvironment in which enzymes are acting when they are immobilized in solid materials is usually quite different from conditions in the bulk solution.…”
Section: From Batch To Continuous Reactors and Process Intensificationmentioning
confidence: 99%
“…302,326 Very recent advances in surface-sensitive spectroscopic techniques have provided evidence that push the determination of enzyme structure and orientation at the solid-liquid interface, in particular single-molecule studies showing that analyses sensitive to temporal and spatial heterogeneities in immobilized enzymes are useful to explain the effects of conformational stability and active-site accessibility on activity. 302,[504][505][506][507] In the interplay with the structural aspects of the immobilized enzyme the microenvironment is the other fundamental aspect determining enzyme performance. The microenvironment in which enzymes are acting when they are immobilized in solid materials is usually quite different from conditions in the bulk solution.…”
Section: From Batch To Continuous Reactors and Process Intensificationmentioning
confidence: 99%
“…Different hydrophobic supports have been used to this purpose, like octyl-agarose beads [ 53 ], decaoctyl sepabeads [ 54 ], silica beads coated with acyl groups, polypropylene [ 55 ], or styrene/styrene divinylbenzene beads [ 17 , 56 ]. The activation of CalB on well-defined modified silica surfaces has been discussed previously in the context of silanized silica surfaces and [ 57 ] SBMA/PEGMA polymer brushes [ 36 ]. It has been suggested that hydrophobic surfaces lead to a more open conformation of CalB giving easier access to the substrate [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hydrophobic surfaces lead to a more open conformation of CalB giving easier access to the substrate [ 57 ]. Yet, in a more generalized computational analysis, it was suggested that the optimum support for individual lipases can be predicted using the free surface energy of solvation as predictor and the mechanism driving hyperactivation exceeds the nature of the lid [ 36 ]. Interestingly, CalB showed the highest free energy of solvation of the lipases under investigation which represents a high hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers whose physical and chemical properties respond to external cues are of widespread interest in many areas, including sensing, drug delivery, actuation, and tissue engineering. , Such materials also have sizable implications in the design of smart materials that readily adapt to their environment, catalyze reactions on demand, and repair and/or regenerate upon damage. Over the past two decades, there has been extensive work on integrating enzymes into polymeric supports to create biocatalytic materials; however, the polymers in such cases have generally been chosen solely for their ability to stabilize enzymes. As a result, such materials have been composed of simple matricese.g., poly­(ethylene glycol), poly­(styrene), polyurethanes, and poly­(methyl methacrylate)that lack functional (e.g., shape-reconfigurable and adaptable/switchable) properties. The scope of materials that could be envisioned would be significantly expanded if the polymer support enhanced the functionality of the enzyme-containing material.…”
Section: Introductionmentioning
confidence: 99%